Cost of raising a replacement dairy heifer from birth to calving - Elizondo-Salazar, Jorge Alberto; Solís-Chaves, Heber Ariel (Agronomía Mesoamericana, 2018)
Dairy heifers are the future of any dairy farm; however, before they begin to produce milk, they represent a very significant cost unknown by an important number of producers. The objective of the present study was to determine the economic cost associated with the rearing of dairy replacements. The study was carried out at the dairy cattle Alfredo Volio Mata Experiment Station of the University of Costa Rica, during the year 2016. A total of forty Jersey heifers were reared from birth to calving (twenty-five months) grouped into three age categories: 0-3 months, 3 to 16 months and 16 to 25 months. In order to determine the total costs within each category, detailed records of all the expenses incurred each day for each animal were kept in an electronic spreadsheet, considering all the activities involved and related to feeding, cleaning and disinfection, veterinary treatments, pasture fertilization, workforce, health management and maintenance, among others. It was determined that the total cost for raising a replacement heifer from birth to calving was ¢818 360.95 (1473.62); representing a 25.17; 53.27 and 21.56% for the stage of birth to three months, three months to service, and service to calving, respectively. Of the total costs, 78.72% corresponded to feed and 6.82% to labor. Depending on milk production and net economic return from each liter of milk produced, the investment would be recovered beyond the second lactation.